Input Bridging Fault and Non Feedback Bridging Fault Detection and Test Vector Generation by Boolean Satisfiability Method - Sarvani, K; Viswanathan, B (International Journal of Engineering and Technology, 2018)
The input bridging faults and non feedback bridging fault( short between lines) occurs due to improper soldering.This paper enumerates the Fault detection and high quality test vector generation for these faults by using Boolean Satisfiability method with the help of JAVA code.This method can be adapted to deal with many faults in the combinational circuits.Â Â